Effect of bio-stimulators on Growth and Yield of Cowpea leaves (Vigna unguiculata Walp) produced in Juja and Katumani in Kenya - Oyoo, Judith; Elijah Ateka, Edward Mamati, Paul Kinoti; Miriam Judith Otipa, James Karanja; Wasilwa, Lusike (Journal of Phytology, 2017)
Bio-stimulators are organic products that have been found to enhance crop growth and productivity through mitigating against biotic and abiotic stresses. Four Cowpea varieties namely K80, M66, KVU 27-1 and Kenya Kunde; commercially released & adopted by local households for vegetable production were used to evaluate the impact of bio-stimulators on growth and leaf yield of cowpea in Juja and Katumani from May to July, 2013. The treatments were arranged in a factorial structure, laid out in an RCBD, which were combination of 9 levels of bio-stimulators, with the 4 cowpea varieties planted per site, and giving a total of 36 treatments for each site replicated 3 times. The plots measured 2.5m by 2.5m with spacing of 60cm by 20cm. Parameters under investigation included germination rate, days to germination, plant height, and number of leaves produced and number of nodules formed. Cultural practices such as weeding and pest control were done as need arose. The results showed that there were significant differences in days to germination, germination rate, plant population, chlorophyll levels, leaf weight, plant height and leaf area but not in leaf area between Juja and Katumani. Earliest germination and highest leaf weight were in Katumai whereas highest plant population, germination rate and chlorophyll levels and leaf area were in Juja. Humates improved germination rate, plant height, leaf weight and nodule development in Juja while seaweed extracts improved days to germination, germination rate, plant height, leaf yield, leaf weight and nodule formation in Katumani. Interaction between site and bio-stimulators was recorded in germination rate, days to germination, plant population and in number of leaves produced. Therefore bio-stimulators should be adopted in production of cowpea leaves particularly offseason for food & nutritional security and increasing household incomes in Kenya